Hubungan Qana’ah dengan Social Comparison pada Mahasiswa Pengguna Tiktok - Iva Nurfaizah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The TikTok app is a popular social media platform in Indonesia, with its main users aged between 18 and 24 years old. This application provides a short video feature that allows users to showcase the lives or lifestyles of other individuals. This often triggers social comparison when someone feels dissatisfied with what they have. The purpose of this study is to determine the relationship between qana'ah and social comparison among TikTok users who are elementary school teacher education students at Swadaya Gunung Jati University in Cirebon. This study uses a quantitative approach with a correlation method. This study used Pearson's correlation to determine the relationship between the two variables. The hypothesis test yielded a result of (rxy = -0.644, p = 0.001). This indicates a significant negative relationship between qana'ah and social comparison, meaning that the higher the level of qana'ah, the lower the level of social comparison. Conversely, the lower the level of qana'ah, the higher the level of social comparison.